2022
DOI: 10.1101/2022.08.13.503858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural principles of B-cell antigen receptor assembly

Abstract: The B-cell antigen receptor (BCR) is composed of a membrane-bound immunoglobulin (mIg) of class M, D, G, A or E for antigen recognition and a disulfide-linked heterodimer between Igα and Igβ (Igα/β, also known as CD79A and CD79B) that functions as the signalling entity. The organizing principle of BCR assembly remains elusive. Here we report the cryo-electron microscopy structures of the intact IgM class BCR at 8.2 Å resolution and its Fab-deleted form (IgM BCRΔFab) at 3.6 Å resolution. At the ectodomain (ECD)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, DeepTMHMM predicted the existence of transmembrane helices at the end of the Tm (Supplementary Figure S3C). Recent reports have shown that B-cell receptors usually have a transmembrane a-helix domain that participates in their assembly (Dong et al, 2022). Given that the hydrophobic core of a typical cell membrane is 3-4 nm in thickness (Frallicciardi et al, 2022), the predicted 21-amino acid transmembrane domain in Tm, forming a roughly 3-nm-long ahelix, should be able to attach the IgNAR short(C3Tm) to the B-cell membrane (Supplementary Figures S3A, C).…”
Section: Structural Analysis Of the Ocellate Spot Skates Ignar And Vnarmentioning
confidence: 99%
“…However, DeepTMHMM predicted the existence of transmembrane helices at the end of the Tm (Supplementary Figure S3C). Recent reports have shown that B-cell receptors usually have a transmembrane a-helix domain that participates in their assembly (Dong et al, 2022). Given that the hydrophobic core of a typical cell membrane is 3-4 nm in thickness (Frallicciardi et al, 2022), the predicted 21-amino acid transmembrane domain in Tm, forming a roughly 3-nm-long ahelix, should be able to attach the IgNAR short(C3Tm) to the B-cell membrane (Supplementary Figures S3A, C).…”
Section: Structural Analysis Of the Ocellate Spot Skates Ignar And Vnarmentioning
confidence: 99%
“…Therefore, this structural arrangement would enable the interaction between FcμR and mIgM on the B-cell membrane. The long-awaited structure of IgM-BCR has been recently unveiled [39][40][41] . Superposing the structure of the FcμR-D1:Fcμ-Cμ4 complex onto that of IgM-BCR reveal that the FcμR-binding site next to Igb is completely exposed (Fig.…”
Section: Crystal Structure Of the Fcμr-d1:fcμ-cμ4 Complexmentioning
confidence: 99%